Crucial influence leadership skills to create lasting behavior change - Grenny, Joseph; Patterson, Kerry, 1946-; Maxfield, David G., 1954-; McMillan, Ron; Switzler, Al (McGraw-Hill Education, 2023)
The New York Times bestselling guide to leading positive change in any organization--updated with critical new insights, research, and case studies The world-renowned leadership experts that brought us the leadership classic Crucial Conversations have fully updated their bestselling Crucial Influence (originally published as Influencer). In these pages, they reveal that fewer than one in eight behavior change efforts is successful--and most produce nothing more than wasted resources and organization-wide cynicism. The solution to this challenge isn't easy, but it is simple. It's all about the strategic application of influence--systematic and intentional actions aimed at helping people improve results by changing their behavior--a practice most leaders have yet to fully understand and embrace. Crucial Influence walks you through the process of identifying the personal, social, and structural levers that influence both motivation and ability, then engaging these levers for directed behavior change. "At the end of the day, leadership is intentional influence," the authors write. "If behavior isn't changing, you aren't leading." Whatever you're seeking to change through effective leadership--from making virtual workforces work to tackling a social issue--influence, not authority, is what will get you there. You'll learn to view leadership through the new lens of influence as you apply the lessons from this book to everyday challenges. New to this edition: Updated stories and examples using the Crucial Influence model The authors' latest research on behavior change Practical applications for everyday leadership challenges New case studies and business examples.